2017
DOI: 10.22161/ijeab/2.4.62
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Goat Farming and Perspectives for a Sustainable Production in Western Africa

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 3 publications
2
21
0
Order By: Relevance
“…Much of the global goat population is concentrated in the arid and semi-arid agro-ecological zones that have frequent droughts and famines [14]. However, these species are reported to be less affected by the harsh climate compared with other ruminants that are highly sensitive to subtle changes in the surrounding environmental fluctuations [15]. Hence, goat rearing is a major source of human nutrition and also the means of economic stability for many small and marginal farmers, providing meat and manure as two major sources of income [14].…”
Section: Goat As Ideal Climate Model Animalmentioning
confidence: 99%
“…Much of the global goat population is concentrated in the arid and semi-arid agro-ecological zones that have frequent droughts and famines [14]. However, these species are reported to be less affected by the harsh climate compared with other ruminants that are highly sensitive to subtle changes in the surrounding environmental fluctuations [15]. Hence, goat rearing is a major source of human nutrition and also the means of economic stability for many small and marginal farmers, providing meat and manure as two major sources of income [14].…”
Section: Goat As Ideal Climate Model Animalmentioning
confidence: 99%
“…Different goat breeds populations found in this region were characterized by long leg and were mainly raised for meat, skin and milk production. In Nigeria and Niger, Red Sokoto goat breed also known as Maradi goat was used for the good quality of its skin [26]. Some exotic breeds such as Alpine (Benin), Anglo-Nubian, Toggenburg, Boer, Saanen (in Nigeria) and Majorera goat (Senegal) have been reported to be kept in West Africa Region under the traditional livestock system [27] [28].…”
Section: Production Systems Of Goats In Ssarmentioning
confidence: 99%
“…These findings are consistent with the price reported by Dossou et al, (2012). The seasonal fluctuation of prices may due to the seasonal variation of fodder and feed resources in term of nutritional value and quantity for lactating cow in farms (Agossou et al, 2017). Indeed, evidence demonstrated that due to high nutritive value and abundance of feed during rainy season, lactating cow produce more milk than during drought season (Soule et al, 2017;Alkoiret et al, 2016).…”
Section: Business Management and Sustainable Competitiveness Of Dairymentioning
confidence: 99%